2019
DOI: 10.1200/jco.2019.37.7_suppl.350
|View full text |Cite
|
Sign up to set email alerts
|

Keynote 057: Phase II trial of Pembrolizumab (pembro) for patients (pts) with high-risk (HR) nonmuscle invasive bladder cancer (NMIBC) unresponsive to bacillus calmette-guérin (BCG).

Abstract: 350 Background: The PD-1 inhibitor pembro has durable antitumor activity in pts with metastatic urothelial carcinoma. Upregulation of the PD-1 pathway has been observed in BCG-resistant NMIBC, suggesting pembro may benefit. Efficacy and safety of pembro in pts with HR, BCG-unresponsive NMIBC was evaluated in the single-arm phase 2 KEYNOTE-057 study; updated results for pts with carcinoma in situ (CIS) with or without papillary tumor (cohort A) are reported. Methods: Pts with histologically confirmed HR, BCG-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(74 citation statements)
references
References 0 publications
0
69
0
5
Order By: Relevance
“…The preliminary outcome of NCT02625961 with 103 patients (median age 73 years; CIS alone 71.8%) has been reported. 68 In the trial, the 3-month CR rate was 38.8%. Among 40 patients with CR at 3 months, 72.5% maintained CR, and stage progression was not observed (median follow-up period 14.0 months).…”
Section: Clinical Trials Of Pd-1/pd-l1 Blockade For Bcg-unresponsive mentioning
confidence: 88%
See 1 more Smart Citation
“…The preliminary outcome of NCT02625961 with 103 patients (median age 73 years; CIS alone 71.8%) has been reported. 68 In the trial, the 3-month CR rate was 38.8%. Among 40 patients with CR at 3 months, 72.5% maintained CR, and stage progression was not observed (median follow-up period 14.0 months).…”
Section: Clinical Trials Of Pd-1/pd-l1 Blockade For Bcg-unresponsive mentioning
confidence: 88%
“…every 3 weeks for 24 months), respectively. The preliminary outcome of NCT02625961 with 103 patients (median age 73 years; CIS alone 71.8%) has been reported . In the trial, the 3‐month CR rate was 38.8%.…”
Section: Clinical Trials Of Pd‐1/pd‐l1 Blockade For Bcg‐unresponsive mentioning
confidence: 99%
“…One patient died as a result of treatment-related colitis. 77 Clinical data included in the package insert for 96 patients on this trial report a complete response rate of 41% (95% CI, 31%-51%) and a median duration of response (DOR) of 16.2 months with 46% of complete responses maintained for at least a year. 78…”
Section: Pembrolizumab For Non-muscle-invasive Bladder Cancermentioning
confidence: 93%
“…Histochemical studies observed that programmed cell death‐1 levels increase in BCG‐relapsing tumors and that PD‐L1 levels are associated with tumor stage progression, both of which suggest impaired T‐cell function. KEYNOTE‐057 is a single‐arm phase 2 study of pembrolizumab in patients with BCG‐unresponsive NMIBC . Among patients with carcinoma in situ with or without papillary disease (n = 103), the 3‐month CR rate was 38.8% (95% CI: 29.4‐48.9), within which 72.5% was maintained at the last 14.0‐month median follow‐up.…”
Section: Bcg‐unresponsive Nmibcmentioning
confidence: 99%